Formation Mechanisms of the Molecular Ion Polar Plume and Its Contribution to Ion Escape From Mars. Issue 6 (3rd June 2022) - Sakakura, Kotaro; Seki, Kanako; Sakai, Shotaro; Sakata, Ryoya; Shinagawa, Hiroyuki; Brain, David A.; McFadden, James P.; Halekas, Jasper S.; DiBraccio, Gina A.; Jakosky, Bruce M.; Terada, Naoki; Tanaka, Takashi
Abstract: We investigated the formation mechanism of a molecular ion plume and its contribution to ion escape based on Mars Atmosphere and Volatile EvolutioN (MAVEN) observations from November 2014 to October 2019 and numerical models. Here, we report a CO2 + ‐rich plume event and a statistical study of the molecular ion plume. MAVEN observed a CO2 + ‐rich plume event, in which the maximum CO2 + escape flux is approximately 4.2 × 10 6 cm −2 s −1, on 28 August 2015 under strong solar wind dynamic pressure conditions. A numerical simulation using strong solar wind dynamic pressure conditions from the event suggested that the molecular ion plume is formed by deep penetration of the solar wind‐induced electric field, which is caused by strong solar wind dynamic pressure. A statistical study showed that CO2 + plume events tend to be observed under high solar wind dynamic pressure and strong electric field conditions. This tendency is consistent with the formation mechanism of the molecular ion plume suggested by the event study. The O2 + plume does not show the same tendency. This is because O2 + ions are abundant in the high‐altitude ionosphere, and O2 + plumes can be formed even under weak solar wind conditions. The subsolar crustal magnetic fields tend to prevent the formation of the molecular ion plume by shielding the ionosphere from the solar wind. The escape rate ratio O + : O 2 + : CO 2 + (O^+:O_2^+:CO_2^+) is approximately 45:53:3 during the whole statistical survey period, suggesting that a molecular ion plume from the ionosphere is a non negligible ion escape channel from Mars. Plain Language Summary: It has been considered that Mars had a thick atmosphere to sustain liquid water on the surface approximately 4 billion years ago, while the Martian atmosphere is thin at the present time. Ion escape to space is one of the candidates that contributes to atmospheric loss. Both atomic oxygen ions (O + ) and molecular ions, such as O2 + and CO2 +, can contribute to ion escape from Mars. However, the escape mechanism and contribution of molecular ions are far from understood. Based on observations by the Mars Atmosphere and Volatile EvolutioN mission, we investigate energetic ion escape channels from Mars, which are accelerated by electric fields. The results show that the strong pressure of the solar wind facilitates energetic molecular ion escape, while crustal magnetization on the Martian surface prevents it. The escape rate ratio O + : O 2 + : CO 2 + (O^+:O_2^+:CO_2^+) is approximately 45:53:3, suggesting the importance of energetic molecular ion escape from Mars. Key Points: When observed, polar plume flux of O 2 + O_2^+ ( CO 2 + CO_2^+ ) is 4 (2) times higher than O +, but they are 4 (23) times less frequently observed than O + The CO 2 + CO_2^+ plume becomes detectable only under high solar wind dynamic pressure conditions, while the O 2 + O_2^+ plume is detected more frequently Subsolar crustal magnetic fields tend to prevent the formation of molecular ion plumes, especially under low dynamic pressure conditions